A combined experimental and computational framework to evaluate the behavior of therapeutic cells for peripheral nerve regeneration. Issue 7 (2nd May 2022) - Eleftheriadou, Despoina; Berg, Maxime; Phillips, James B.; Shipley, Rebecca J.
Abstract: Recent studies have explored the potential of tissue‐mimetic scaffolds in encouraging nerve regeneration. One of the major determinants of the regenerative success of cellular nerve repair constructs (NRCs) is the local microenvironment, particularly native low oxygen conditions which can affect implanted cell survival and functional performance. In vivo, cells reside in a range of environmental conditions due to the spatial gradients of nutrient concentrations that are established. Here we evaluate in vitro the differences in cellular behavior that such conditions induce, including key biological features such as oxygen metabolism, glucose consumption, cell death, and vascular endothelial growth factor secretion. Experimental measurements are used to devise and parameterize a mathematical model that describes the behavior of the cells. The proposed model effectively describes the interactions between cells and their microenvironment and could in the future be extended, allowing researchers to compare the behavior of different therapeutic cells. Such a combinatorial approach could be used to accelerate the clinical translation of NRCs by identifying which critical design features should be optimized when fabricating engineered nerve repair conduits. Abstract : Combining in vitro experiments and mathematical modeling to quantify the behavior of therapeutic cells in peripheral nerve injury repair scenarios.